Dasar-Dasar Komunikasi Bisnis - Zein Adin (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. Communication in the business world is used to build partnerships, intellectual resources, to promote an idea, product, service, or an organization, with the aim of creating value for the business being run. According to Purwanto, business communication is communication used in the business world which includes various forms of communication, verbal or non-verbal communication to achieve certain goals. In this sense of communication, it includes the party communicating and something being communicated. The nature of communication includes oral, written, non-verbal communication through gestures or gestures, namely body language, or through symbols and pictures. Verbal communication is used in the business world to convey business messages to other parties either in writing or orally, while non-verbal communication is more spontaneous than verbal communication in terms of conveying a message. Abstrak. Komunikasi dalam dunia bisnis digunakan untuk membangun Partnership, sumberdaya intelektual , untuk mempromosikan satu gagasan, produk, servis, atau suatu organisasi,dengan sasaran untuk menciptakan nilai bagi bisnis yang dijalankan. Menurut purwanto komunikasi bisnis adalah komunikasi yang digunakan dalam dunia bisnis yang mencakup berbagai macam bentuk komunikasi, komunikasi verbal ataupun komunikasi non verbal untuk mencapai tujuan tertentu. Dalam pengertian komunikasi ini tercakup pihak yang berkomunikasi dan sesuatu yang dikomunikasikan. Sifat komunikasi meliputi komunikasi lisan, tulisan, komunikasi non-verbal melalui kial atau gestural yaitu Bahasa tubuh, atau melalui symbol dan gambar-gambar. Komunikasi verbal digunakan dalam dunia bisnis untuk menyampaikan pesan-pesan bisnis kepada pihak lain baik secara tertulis (written) maupun lisan (oral) sedangkan komunikasi non verbal lebih bersifat spontan dibandingkan dengan komunikasi verbal dalam hal penyampaian suatu pesan.